1981
DOI: 10.4319/lo.1981.26.4.0795
|View full text |Cite
|
Sign up to set email alerts
|

A device for the measurement of infiltration in intermittently flooded wetlands1

Abstract: An infiltrometer has been designed to measure infiltration and exfiltration in intermittently or continuously inundated soils, such as occur in tidal salt marshes. The device isolates a column of water while actively maintaining natural head conditions, and yields infiltration/exfiltration rates from mass balance considerations. It incorporates a Stevens recorder, a reversible positive‐displacement metering pump, and solid‐state circuitry. It can detect <5 mm of infiltration or exfiltration per tidal cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Vertical flow can be generated at rising tide by overlying water infiltrations or water discharge to the overlying waters [22,23]. Infiltrations may either take place when water fills empty pore spaces above the water table [24], when cold overlying waters mix with porewaters warmed at low tide during the day [25], or as a result of the interaction of overlying water flow and rippled beds or mounds [21]. Simultaneously, vertical flow can also be generated at ebb tide if the hydrostatic pressure is increased at depth and forces the porewaters to the surface [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vertical flow can be generated at rising tide by overlying water infiltrations or water discharge to the overlying waters [22,23]. Infiltrations may either take place when water fills empty pore spaces above the water table [24], when cold overlying waters mix with porewaters warmed at low tide during the day [25], or as a result of the interaction of overlying water flow and rippled beds or mounds [21]. Simultaneously, vertical flow can also be generated at ebb tide if the hydrostatic pressure is increased at depth and forces the porewaters to the surface [24].…”
Section: Introductionmentioning
confidence: 99%
“…Infiltrations may either take place when water fills empty pore spaces above the water table [24], when cold overlying waters mix with porewaters warmed at low tide during the day [25], or as a result of the interaction of overlying water flow and rippled beds or mounds [21]. Simultaneously, vertical flow can also be generated at ebb tide if the hydrostatic pressure is increased at depth and forces the porewaters to the surface [24]. Vertical flow is usually favored in marshes with flat topography, in coarse-grained sediments, in rippled sediments, or in confined zones such as creeks surrounded by banks.…”
Section: Introductionmentioning
confidence: 99%
“…The only attempt to directly measure infiltration (and exfiltration) was that by Hemond et al (1984) who found that this component of the water balance in a New England marsh amounted to only a few millimeters per tidal inundation. Given the elaborate instrumentation required for such measurements (Hemond and Burke, 1981), it is not surprising that subsequent studies have resorted to theory and calculation in estimating this flux.…”
Section: Introductionmentioning
confidence: 99%
“…The infiltration measurements at the two marshes were accomplished with a new design of active infiltrometer, which isolates a column of water on the marsh surface while duplicating natural head conditions [Hemond and Burke, 1981].…”
Section: Direct Infiltration Measurementmentioning
confidence: 99%